2020
DOI: 10.1093/carcin/bgaa033
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress enhances NNK-induced lung tumors in A/J mice

Abstract: Children born to women who experience stress during pregnancy have an increased risk of cancer in later life, but no previous animal studies have tested such a link. We questioned whether prenatal stress (PS) in A/J mice affected the development of lung tumors after postnatal response to tobacco-specific nitrosamine, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK). Timed-bred A/J mice were randomly assigned on gestation day 12.5 to PS by restraint for 5 consecutive days or control (no restraint). Adult of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Additionally, prenatally stressed mice have significantly increased the number of lung proliferations and area of lesions microscopically compared to the control mice 10) . Immunohistochemically, CD3-positive T cells and Foxp3-positive T cells were evaluated and prenatally stress exposed adult mice had significantly more CD3positive T cells within lung lesions 10) . It is suggested that prenatal stress induces not only early carcinogenesis in offspring but also changes in the tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Additionally, prenatally stressed mice have significantly increased the number of lung proliferations and area of lesions microscopically compared to the control mice 10) . Immunohistochemically, CD3-positive T cells and Foxp3-positive T cells were evaluated and prenatally stress exposed adult mice had significantly more CD3positive T cells within lung lesions 10) . It is suggested that prenatal stress induces not only early carcinogenesis in offspring but also changes in the tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 93%
“…It has been proposed that maternal stress during pregnancy has been linked to cancer in offspring, such as colon cancer and leukemia 3) . In the animal model of lung cancer (A/J mouse), offspring in the prenatal stress group had more proliferative lesions in lung macroscopically compared to offspring in control 10) . Additionally, prenatally stressed mice have significantly increased the number of lung proliferations and area of lesions microscopically compared to the control mice 10) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations